2011
DOI: 10.1371/journal.pone.0025836
|View full text |Cite
|
Sign up to set email alerts
|

The Mitochondrial Genomes of the Early Land Plants Treubia lacunosa and Anomodon rugelii: Dynamic and Conservative Evolution

Abstract: Early land plant mitochondrial genomes captured important changes of mitochondrial genome evolution when plants colonized land. The chondromes of seed plants show several derived characteristics, e.g., large genome size variation, rapid intra-genomic rearrangement, abundant introns, and highly variable levels of RNA editing. On the other hand, the chondromes of charophytic algae are still largely ancestral in these aspects, resembling those of early eukaryotes. When the transition happened has been a long-stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
85
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(96 citation statements)
references
References 82 publications
11
85
0
Order By: Relevance
“…In liverworts, both Haplomitrium [38] and Treubia [27] retain a functional mitochondrial nad7 gene, while all other species investigated have pseudogenised copies, varying greatly in their degrees of degeneration but remarkable for having persisted throughout the long evolutionary history of the group [38]. This is consistent with current hypotheses of Haplomitrium and Treubia forming the sister clade (Haplomitriopsida) to the rest of the liverworts (Marchantiopsida and Jungermanniopsida, e.g.…”
Section: Discussionsupporting
confidence: 78%
“…In liverworts, both Haplomitrium [38] and Treubia [27] retain a functional mitochondrial nad7 gene, while all other species investigated have pseudogenised copies, varying greatly in their degrees of degeneration but remarkable for having persisted throughout the long evolutionary history of the group [38]. This is consistent with current hypotheses of Haplomitrium and Treubia forming the sister clade (Haplomitriopsida) to the rest of the liverworts (Marchantiopsida and Jungermanniopsida, e.g.…”
Section: Discussionsupporting
confidence: 78%
“…The plastid genomes of the closest Polytrichum species have a GC percentage of 28% to 33% [21,22] and those of seed plants range between 34% and 40% [50]. Cai et al, observed high G + C contents in the chloroplast coding regions, and certain regions had higher percentages than others, such as the IR region with its four genes with high levels of G and C [51]. Thus, the distribution of GC content in the chloroplast is unequal, and, perhaps, the higher content presented by the Polytrichaceae species refers to the significant number of coding regions scaffolded.…”
Section: Discussionmentioning
confidence: 99%
“…Flowering plant mitogenomes exemplify the former, with substantial variation in genome size and structure even among close relatives (Francis and Fernand, 1977;Alverson et al, 2010;Tang et al, 2015;Chen et al, 2017). They have highly variable intergenetic regions containing diverse repeated sequences (Kitazaki and Kubo, 2010), frequent structural rearrangements (Galtier, 2011), massive genes loss, frequent endogenous and foreign DNA transfer (Bergthorsson et al, 2003;Kubo and Newton, 2008;Hao and Palmer, 2009;Bock, 2010;Liu et al, 2011), and a highly variable RNA editing process (Takenaka et al, 2008). Conversely, plant mitochondrial genes display exceptionally low rates of nucleotide substitution (Wolfe et al, 1987;Palmer et al, 2000;Mower et al, 2007;Galtier, 2011).…”
Section: Plant Mitochondrial Genome Evolution and Cytoplasmic Male Stmentioning
confidence: 99%